"The Impact of the Financing Structure on the Marcket Share of Private Insurance Companies in Syria" (Journal of Hama University, 2022)
This study addresses the problem of enhancing competitiveness from market share side through the financing structure combination of insurance companies and aims to analyze and discuss the impact of the funding structure on enhancing competitiveness, assuming a statically significant impact for each of independent variables reflecting the funding structure ( internal finance ratio, external finance ratio ) in dependent variable reflecting competitiveness (market share) using a simple regression analysis method to examine the relationship between each independent variable and dependent variable on the statistical analysis program SPSS during the period from 2010 to 2020 for private commercial insurance companies listed on the Damascus stock exchange. The study concluded that there is statistically significant positive relationship for the external finance ratio in the market share of SKIC, NIU companies because of the increase in insurance premiums in these companies, while there was no such effect in the rest of companies.And a statistically significant inverse relationship to the internal finance ratio in the market share of SKIC, NIU companies, the most important recommendations are to rise internal finance ratio to give the companies the possibility to accept greater insurance risks and thereby increase insurance premiums and profitability  in order to enhance its competitiveness.
Keywords: financing structure, insurance companies, market share.